Efektivitas Pemberian Sayur Bayam Hijau (Amaranthus gangeticus) terhadap Peningkatan Hemoglobin pada Ibu Menyusui - Sandra G.J Tombokan; Freike S.N Lumy; Jein Y Bawia; Dian Pratiwi (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background: Anemia is one of the most indirect causes of bleeding in women giving birth. In Indonesia, mortality in postpartum mothers due to anemia reaches 30%. Breastfeeding mothers are one of the groups that are included in the nutritional vulnerable group. With the lack of food intake in certain types of food, the mother experiences a deficiency of certain types of nutrients. Spinach leaves are efficacious to prevent anemia because they are rich in iron. The iron content in spinach plays a role in the formation of hemoglobin. Objective: The purpose of this study was to determine the effectiveness of giving green spinach to increase hemoglobin in breastfeeding mothers. Methods: This type of research is Quasi Experimental Design technique one group pre test post test Samples were taken by accidental sampling , namely 20 breastfeeding mothers. Data analysis with Paired Sample T Test. Results: Shows that the average hemoglobin level of breastfeeding mothers before giving green spinach increases after giving green spinach by .test Statistical explained that there was an effect of giving green spinach to the hemoglobin level of breastfeeding mothers. Recommendations for breastfeeding mothers to consume green spinach as an effort to increase hemoglobin.